Diastereoselective acylation of 3, 4-dihydro-3-methyl-2H-[1, 4]benzoxazines with 2-phenoxy carbonyl chlorides. Issue 5 (28th March 2015) - Vakarov, Sergey A.; Gruzdev, Dmitry A.; Sadretdinova, Liliya Sh.; Chulakov, Evgeny N.; Pervova, Marina G.; Ezhikova, Marina A.; Kodess, Mikhail I.; Levit, Galina L.; Krasnov, Victor P.
Graphical abstract: Abstract: In the search for novel efficient chiral resolving agents, we have studied the diastereoselective acylation of 3, 4-dihydro-3-methyl-2 H -[1, 4]benzoxazine and 7, 8-difluoro-3, 4-dihydro-3-methyl-2 H -[1, 4]benzoxazine with acyl chlorides of 2-phenoxy carboxylic acids (2-phenoxypropionic, 2-phenoxyisovaleric, and 2-phenoxy-3-phenylpropionic) in toluene and dichloromethane at different temperatures. HPLC analysis of the acylation products showed the predominant formation of ( R ∗, S ∗ )-diastereoisomeric amides in all cases. It was found that acylation with the studied acyl chlorides was highly stereoselective; 2-phenoxyisovaleryl chloride demonstrated the highest stereoselectivity (selectivity factor s up to 499). A model for the diastereoisomeric transition states in the interaction between racemic amine and acyl chloride is proposed. Abstract : ( S )-2-Phenoxypropionic acid: C9 H10 O3 ee 70% [ α ]D 20 = −15.1 ( c 1.0, CHCl3 ) Source of chirality: kinetic resolution Absolute configuration: (2 S ) Abstract : ( S )-2-Phenoxyisovaleric acid: C11 H14 O3 ee 91% [ α ]D 20 = −28.2 ( c 1.0, CHCl3 ) Source of chirality: kinetic resolution Absolute configuration: (2 S )